Oil-dispersible MHCF nano-particles as well as preparation method and application thereof

By using oil dispersible MHCF nanoparticles as counter electrode materials, the problem of polymer electrochromic devices lacking high-performance counter electrode materials is solved, and a counter electrode film with high transmittance and electrochromic characteristics is achieved, which improves the overall performance of the device.

CN120081391APending Publication Date: 2025-06-03SHANGHAI RONGKE SPECIAL EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510242769.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

Existing polymer electrochromic devices lack high-performance counter-electrode materials, resulting in high driving voltage, slow response speed and short service life.

Method used

Oil dispersible MHCF nanoparticles are used as counter electrode materials and prepared by co-precipitation and surface modification methods to achieve good dispersion of nanoparticles in organic solvents, forming a counter electrode film with high transmittance and electrochromic characteristics.

Benefits of technology

It improves the comprehensive performance of polymer electrochromic devices, reduces driving voltage, improves response speed and service life, and achieves high transmittance and electrochromic characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120081391A_ABST
    Figure CN120081391A_ABST
Patent Text Reader

Abstract

The invention provides an oil-dispersible MHCF nano-particle as well as a preparation method and application of the oil-dispersible MHCF nano-particle. The material is oil-dispersible hexacyanoferrate metal (MHCF) nanoparticles, the molecular formula of the oil-dispersible hexacyanoferrate metal (MHCF) nanoparticles is KM [Fe (CN) 6], and M is one or more of nickel, vanadium, chromium, molybdenum, tungsten, manganese, iron, ruthenium, cobalt, platinum and copper metal elements. The preparation method comprises the following steps: firstly, mixing an aqueous solution of an anionic metal cyano complex containing a metal atom Fe as a central metal with an aqueous solution of metal cations containing a metal atom M, and carrying out coprecipitation to obtain Prussian blue type MHCF nanoparticles; secondly, a solution obtained by dissolving a ligand in a solvent is mixed with the MHCF nano-particles for surface modification, and oil-dispersible NiHCF nano-particles dispersed in the mixed solution are obtained; and finally, carrying out post-treatment on the solution after the reaction, so as to obtain the oil-dispersible MHCF nano-particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochromic materials, and particularly relates to an oil-dispersible MHCF nanoparticle, a preparation method thereof, and an application thereof. Background Art

[0002] Electrochromic devices (ECDs) can reversibly adjust their optical properties when an external potential is applied, and have broad application potential in the fields of smart windows, adaptive camouflage, skylights, etc. As an important component of electrochromic devices, a suitable counter electrode is crucial for obtaining high-performance ECDs, which can significantly reduce the operating voltage, improve the switching speed and stability.

[0003] Traditional counter electrode materials (such as metal oxides, conductive polymers) have problems such as insufficient electrochemical activity, color residue, complex preparation or high cost. Prussian blue analogs have attracted much attention due to their excellent electrochemical properties, adjustable structure, and simple preparation, but their poor dispersibility and weak film-forming ability limit their applications.

[0004] In the prior art, polymer electrochromic devices (PECDs) lack high-performance counter electrode materials, resulting in high device driving voltage, slow response speed, and short service life. Summary of the Invention

[0005] The purpose of the present invention is to overcome the defects existing in the prior art, and provide an oil-dispersible MHCF nanoparticle, a preparation method thereof, and an application thereof, which break through the limitations of poor dispersibility and weak film-forming ability of existing Prussian blue-based materials, solve the problem of the lack of high-performance counter electrode materials in polymer electrochromic devices, and improve the comprehensive performance of polymer electrochromic devices.

[0006] The technical solution of the present invention is to first provide an oil-dispersible MHCF nanoparticle, the molecular formula of which is KM[Fe(CN) 6 , where M is one or more of the metal elements of nickel, vanadium, chromium, molybdenum, tungsten, manganese, iron, ruthenium, cobalt, platinum, and copper; the oil dispersibility means that in the absence of any other additives, the MHCF nanoparticles are dispersed in an organic solvent to obtain a clear, transparent, and precipitate-free solution; the average particle size of the MHCF nanoparticles is less than 50 nm.

[0007] The present invention also provides a preparation method for the above-mentioned oil-dispersible MHCF nanoparticles, including the following steps:

[0008] (a) Mix an aqueous solution containing an anionic metal cyanide complex with a metal atom Fe as the central metal and an aqueous solution containing a metal cation compound of a metal atom M, and carry out a coprecipitation reaction at room temperature to generate MHCF nanoparticles;

[0009] (b) Mix the solution of ligand L dissolved in a solvent with the MHCF nanoparticle suspension obtained from step (a) for surface modification to obtain oil-dispersible MHCF nanoparticles dispersed in the mixed solution;

[0010] (c) Post-treat the solution obtained in step (b) to obtain the oil-dispersible MHCF nanoparticles.

[0011] Furthermore, in the above step (a): the anionic metal cyanide complex with metal atom Fe as the central metal is Na 3 Fe(CN) 6 or K 3 Fe(CN) 6 ; the anion of the metal cation compound containing metal atom M is one of SO 4 2- , NO 3- , Cl - , where M is one of nickel, vanadium, chromium, molybdenum, tungsten, manganese, iron, ruthenium, cobalt, platinum and copper; the molar ratio of the anionic metal cyanide complex with metal atom Fe as the central metal to the metal cation compound containing metal atom M is 1 - 1.5:1.

[0012] Furthermore, the temperature of the coprecipitation reaction in the above step (a) is 25 °C, and the reaction time is 3 - 5 h.

[0013] Furthermore, in the above step (b): ligand L is oleylamine or stearylamine; the solvent for dissolving ligand L is one of toluene, dichloromethane, chloroform, hexane, and ether.

[0014] Furthermore, in the above step (b): the addition amount of ligand L relative to the total amount of metal atom Fe and metal atom M in the MHCF nanoparticles obtained in step (a)) is (Fe + M):L = 1:0.2 - 1:2 in terms of molar ratio; the amount of solvent used for dissolving ligand L is 1:5 - 1:50 in terms of mass ratio, ligand L:solvent; the MHCF nanoparticle suspension is obtained by dispersing the MHCF nanoparticles obtained in step (a) with water, and the addition amount of water is 3:1 - 5:1 in terms of volume ratio of solvent:water to the solvent of ligand L.

[0015] Furthermore, in the above step (b): the temperature of surface modification is 25 °C, and the reaction time is 1 - 3 h.

[0016] Furthermore, the method of the above step (c) is: extract the mixture obtained in step (b) with the solvent of ligand L, filter the extracted solution with diatomaceous earth, and then rotary evaporate to remove the remaining solvent to obtain the oil-dispersible MHCF nanoparticles.

[0017] The present invention also provides an MHCF thin film, which is formed by dissolving the oil-dispersible MHCF nanoparticles provided by the present invention in a solvent, spraying the solution, and then cleaning and drying it with acetone. The thickness of the thin film is 400 - 900 nm.

[0018] The present invention further provides an MHCF counter electrode thin film, which is formed by dissolving the oil-dispersible MHCF nanoparticles provided by the present invention in a solvent, spraying the solution on a transparent conductive substrate, and then cleaning and drying it with acetone. The thickness of the thin film is 400 - 900 nm. The MHCF counter electrode thin film has a transmittance of 50% - 99% in the visible light band of 500 nm - 800 nm; and exhibits an anodic coloring electrochromic property during the electrochemical oxidation-reduction process. The above high transmittance property and color change property of the MHCF counter electrode thin film, combined with its electrochemical activity, are particularly suitable for polymer electrochromic research and the development of polymer electrochromic devices.

[0019] The present invention further provides a polymer electrochromic device, which includes a transparent conductive electrode layer, an electrochromic polymer layer, an electrolyte layer, and a counter electrode layer stacked in sequence, wherein the counter electrode layer is formed by the oil-dispersible MHCF nanoparticles provided by the present invention on a transparent conductive substrate.

[0020] The advantages and beneficial effects of the present invention compared with the prior art are as follows:

[0021] 1) Based on the premise of improving the performance of polymer electrochromic devices and on the basis of the Prussian blue-type structure, the present invention introduces electrochemically inert nickel elements. The Ni atoms and Fe atoms are connected by cyano groups to form a three-dimensional crosslinking of the NaCl-type lattice. When the synthesized NiHCF crystal structure undergoes an oxidation-reduction reaction, it can not only resist the stress caused by the insertion and extraction of alkali metal ions, having excellent stability; but also store and release the ions required for the oxidation-reduction reaction of electrochromic polymers, having excellent ion storage capacity. Since Prussian blue-type compounds have special structural tunability, the Ni atoms connected to Fe atoms through cyano groups can be replaced. Therefore, nickel elements can be changed to one or more metal elements such as vanadium, chromium, molybdenum, tungsten, manganese, iron, ruthenium, cobalt, nickel, platinum, and copper as M atoms. The M atoms connected to Fe atoms through cyano groups can form various single-element or multi-element Prussian blue-type counter electrode materials MHCF.

[0022] 2) In the preparation method of the present invention, the disadvantages of poor dispersibility and difficult film formation of Prussian blue-type compounds are overcome by surface modification methods, enabling the MHCF nanoparticles to be well dispersed in organic solvents such as toluene and chloroform, which is conducive to large-area film formation.

[0023] 3) The extraction in step (c) is to extract the oil-dispersible MHCF nanoparticles dispersed in the mixed solvent; the use of diatomaceous earth filtration is to filter out the aggregates of MHCF nanoparticles that have not been successfully modified; the excess solvent is removed by rotary evaporation to facilitate the redispersion of the oil-dispersible MHCF nanoparticles in the required organic solvent.

[0024] 4) The counter electrode film based on the oil-dispersible MHCF nanoparticles of the present invention has a high transmittance in the visible light band (300 - 800 nm), especially a transmittance of 50% - 99% in the range of 500 - 800 nm; and exhibits an anodically coloring electrochromic property during the electrochemical oxidation-reduction process.

[0025] The present invention provides a Prussian blue-based material suitable for the counter electrode of polymer electrochromic devices. By changing the type of metal atoms and surface modification, a counter electrode film with excellent ion storage capacity and transmittance is obtained. In addition, the preparation method of the present invention is suitable for the preparation of various Prussian blue-based counter electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] From the following detailed description of the embodiments of the present invention in conjunction with the drawings, these and / or other aspects and advantages of the present invention will become clearer and easier to understand, where:

[0027] Figure 1 is the X-ray diffraction pattern of the counter electrode material NiHCF nanoparticles obtained in Example 1 of the present invention;

[0028] Figure 2 is the spectral absorption curve of the oil-dispersible Prussian-type nanoparticles obtained in Examples 1 - 4 of the present invention dissolved in chloroform;

[0029] Figure 3 is the optical photograph of the oil-dispersible Prussian-type nanoparticles obtained in Examples 1 - 4 of the present invention dissolved in chloroform;

[0030] Figure 4 is the scanning electron microscope image of the unmodified NiHCF powder and the modified NiHCF film before surface modification obtained in Example 1 of the present invention;

[0031] Figure 5 is the transmittance spectrum of the NiHCF counter electrode film obtained in Example 1 of the present invention at different potentials;

[0032] Figure 6 is the cyclic voltammogram of the NiHCF counter electrode film and different electrochromic polymer films obtained in Example 1 of the present invention;

[0033] Figures 7 - 10 is the square wave potential cycling diagram of the blue, orange, red, and black polymer electrochromic devices obtained in Example 1 of the present invention at their characteristic wavelengths;

[0034] Figures 11 - 13 It is the square wave potential cycling diagram of the corresponding blue polymer electrochromic devices of FeHCF, CoHCF, and CuHCF obtained in Examples 2-4 of the present invention at their characteristic wavelengths. Detailed implementation manners

[0035] The following combines examples and the accompanying drawings of the specification to further describe the detailed implementation manners of the present invention. The following examples are only used to more clearly illustrate the technical solutions of the present invention and cannot be used to limit the protection scope of the present invention.

[0036] Example 1

[0037] (1) Preparation of oil-dispersible NiHCF nanoparticles

[0038] An aqueous solution of 0.329 g of K 3 [Fe(CN) 6 dissolved in water and an aqueous solution of 0.238 g of NiCl 2 .6H 2 O dissolved in water were mixed, and a coprecipitation reaction was carried out at room temperature for 5 hours to precipitate microcrystals of NiHCF (KNi[Fe(CN) 6 ). The water-insoluble NiHCF microcrystals were separated by centrifugation, washed 3 times with water, then washed 2 times with ethanol, and dried under reduced pressure.

[0039] The results of analyzing the prepared NiHCF crystals with a powder X-ray diffractometer are shown in Figure 1 . This is consistent with KNi[Fe(CN) 6 retrieved from the standard sample database.

[0040] 0.177 g of the prepared NiHCF nanoparticles were added to a mixed solution composed of 0.5 ml of water, 5 ml of toluene, and 0.135 g of oleylamine. After reacting vigorously at room temperature for 3 h, a yellow-brown solution was obtained. After extraction with toluene and filtration through diatomaceous earth, a final yellow-brown transparent solution was obtained, indicating that the NiHCF nanoparticles were well dispersed in toluene. The oil-dispersible NiHCF nanoparticles could be obtained by removing toluene through rotary evaporation.

[0041] Figure 2 The solution spectrum of the oil-dispersible NiHCF nanoparticles redispersed in chloroform is shown. Figure 3 (a) is its solution optical photograph. Due to the charge transfer of Ni-CN-Fe, an obvious absorption peak appears near 400 nm, presenting yellow. In addition, it can be seen from the solution optical photograph that the oil-dispersible NiHCF is fully dispersed in chloroform without any particle precipitation.

[0042] (2) Preparation of NiHCF counter electrode film

[0043] Disperse the oil-dispersible NiHCF nanoparticles in chloroform to prepare a 20 mg / ml solution, place it in a spray gun, control the air pressure at 2 MPa, and spray it on the conductive glass. The film thickness is about 500 nm. After spraying, dry the film in a forced-air drying oven at 100 °C for 20 minutes and cool it to room temperature, then rinse it with acetone and dry it again for 5 minutes, and take it out and cool it to room temperature.

[0044] Figure 4 (a) SEM image of NiHCF powder before modification, Figure 4 (b) and (c) SEM images of NiHCF film after modification. By comparison, it can be seen that surface modification can make the NiHCF nanoparticles evenly distributed, improving the film quality; and the average particle size of the well-dispersed NiHCF nanoparticles after modification is below 50 nm.

[0045] Perform spectral and electrochemical performance tests on the NiHCF film at different voltages. Adopt a three-electrode system, with a platinum wire as the counter electrode, a calibrated silver wire as the reference electrode, the NiHCF film as the working electrode, and the supporting electrolyte as: 0.1 mmol / L lithium perchlorate propylene carbonate solution.

[0046] The spectra of the NiHCF film at different applied voltages are as Figure 5 shown, indicating that the NiHCF film has excellent transmittance in the visible light range.

[0047] Figure 6 The cyclic voltammograms of the NiHCF film and different electrochromic polymer films at the same scan rate are shown. It can be seen that the NiHCF film has an electrochemical window that matches well with the electrochromic polymer film, and an ion storage capacity sufficient to support the redox reaction of the electrochromic polymer.

[0048] (3) Preparation of polymer electrochromic devices

[0049] Use blue, orange, red, and black polymers as electrochromic layers, and ultraviolet-cured gel electrolyte as the electrolyte layer, and assemble them with the NiHCF counter electrode film into different polymer electrochromic devices.

[0050] Figures 7 - 10It is a square wave potential cycling diagram of corresponding blue, orange, red, and black electrochromic devices at their characteristic wavelengths. It can be found that the fabricated electrochromic devices all have high contrast and fast response time. The highest contrast can reach 61%, and the coloring / bleaching time can be as fast as 1.7 / 1.6 seconds at the fastest. This indicates that the NiHCF counter electrode film is adaptable to multi-band electrochromic polymers, and the fabricated electrochromic devices have excellent performance.

[0051] In addition, as shown in Table 1 (comparison of the product performance of each color-changing device made of the counter electrode obtained in Example 1 and the color-changing device products made of counter electrodes of other materials), through comparative analysis with the prior art using PEDOT:PSS as the counter electrode or MCCP as the counter electrode, it can be known that the electrochromic device prepared using the oil-dispersible NiHCF nanoparticles of the present invention as the counter electrode has more excellent performance. The fabricated electrochromic device has a lower driving voltage, fast coloring / bleaching time, high contrast, and excellent cycle stability.

[0052] Example 2

[0053] (1) Preparation of oil-dispersible FeHCF nanoparticles

[0054] Dissolve 0.329 g of K 3 [Fe(CN) 6 in an aqueous solution and mix it with an aqueous solution of 0.199 g of FeCl 2 ·4H 2 O dissolved in water. Carry out a coprecipitation reaction at room temperature for 3 hours to precipitate microcrystals of FeHCF (KFe[Fe(CN) 6 ). Separate the water-insoluble FeHCF microcrystals by centrifugation, wash them 3 times with water, then wash them 2 times with ethanol, and dry them under reduced pressure. Add 0.2 g of the prepared FeHCF nanoparticles to a mixed solution composed of 0.5 ml of water, 5 ml of dichloromethane, and 0.109 g of oleylamine. After reacting vigorously at room temperature for 3 h, a dark blue solution is obtained. After extraction with dichloromethane and filtration through diatomaceous earth, the final dark blue transparent solution is obtained, indicating that the FeHCF nanoparticles are well dispersed in dichloromethane. The oil-dispersible FeHCF nanoparticles can be obtained by removing dichloromethane through rotary evaporation.

[0055] Figure 2 The solution spectrum of the oil-dispersible FeHCF nanoparticles redispersed in chloroform is shown, Figure 3 (b) is its solution optical photograph. Due to the charge transfer of Fe-CN-Fe, an obvious absorption peak appears near 700 nm, showing blue. In addition, it can be seen from the solution optical photograph that the oil-dispersible FeHCF is fully dispersed in chloroform without any particle precipitation.

[0056] (2) Preparation of Polymer Electrochromic Device

[0057] Using a blue polymer as the electrochromic layer and an ultraviolet-curable gel electrolyte as the electrolyte layer, an electrochromic device is assembled with an FeHCF counter electrode film. Figure 11 Correspondingly, it is the square-wave potential cycling diagram of the blue electrochromic device at its characteristic wavelength.

[0058] Example 3

[0059] (1) Preparation of Oil-Dispersible CoHCF Nanoparticles

[0060] Dissolve 0.329 g of K 3 [Fe(CN) 6 in an aqueous solution and mix it with an aqueous solution of 0.238 g of CoCl 2 ·6H 2 O dissolved in water. Carry out a coprecipitation reaction at room temperature for 4 hours to precipitate microcrystals of CoHCF (KCo[Fe(CN) 6 ). Separate the water-insoluble CoHCF microcrystals by centrifugation, wash them 3 times with water, then wash them 2 times with ethanol, and dry them under reduced pressure.

[0061] Add 0.2 g of the prepared CoHCF nanoparticles to a mixed solution composed of 0.5 ml of water, 5 ml of toluene, and 0.109 g of stearylamine. After reacting vigorously for 3 h, a purple solution is obtained. After extraction with toluene and filtration through diatomaceous earth, a final transparent purple solution is obtained, indicating that the CoHCF nanoparticles are well dispersed in toluene. The oil-dispersible CoHCF nanoparticles can be obtained by removing toluene through rotary evaporation.

[0062] Figure 2 The solution spectrum of the oil-dispersible CoHCF nanoparticles redispersed in chloroform is shown, Figure 3 (c) is its solution optical photograph. Due to the charge transfer of Co-CN-Fe and Fe-Fe, obvious absorption peaks appear near 380 and 550 nm, presenting a purple color. In addition, it can be seen from the solution optical photograph that the oil-dispersible CoHCF is fully dispersed in chloroform without any particle precipitation.

[0063] (2) Preparation of Polymer Electrochromic Device

[0064] Using a blue polymer as the electrochromic layer and an ultraviolet-curable gel electrolyte as the electrolyte layer, an electrochromic device is assembled with a CoHCF counter electrode film. Figure 12 It is the square-wave potential cycling diagram of the corresponding blue electrochromic device at its characteristic wavelength.

[0065] Example 4

[0066] (1) Preparation of oil-dispersible CuHCF nanoparticles

[0067] Dissolve 0.329 g of K 3 [Fe(CN) 6 in an aqueous solution and mix it with an aqueous solution of 0.134 g of CuCl 2 dissolved in water to precipitate microcrystals of CuHCF (KCu[Fe(CN) 6 ). The water-insoluble CuHCF microcrystals are separated by centrifugation, washed three times with water, then washed twice with ethanol, and dried under reduced pressure.

[0068] Add 0.2 g of the prepared CuHCF nanoparticles to a mixed solution composed of 0.5 ml of water, 5 ml of hexane, and 0.107 g of stearylamine. After reacting vigorously for 3 h, a brown solution is obtained. After extraction with hexane and filtration through diatomaceous earth, a final brown transparent solution is obtained, indicating that the CuHCF nanoparticles are well-dispersed in toluene. The oil-dispersible CuHCF nanoparticles can be obtained by removing hexane by rotary evaporation.

[0069] Figure 2 The solution spectrum of the oil-dispersible nanoparticles redispersed in chloroform is shown, Figure 3 (d) is the optical photograph of its solution. Due to the charge transfer of Cu-CN-Fe and Fe-Fe, obvious absorption peaks appear near 480 and 720 nm, presenting a brown color. In addition, it can be seen from the optical photograph of the solution that the oil-dispersible CuHCF is fully dispersed in chloroform without any particle precipitation.

[0070] (2) Preparation of polymer electrochromic devices

[0071] Use a blue polymer as the electrochromic layer and an ultraviolet-curable gel electrolyte as the electrolyte layer, and assemble them with a CuHCF counter electrode film into an electrochromic device. Figure 13 is the square wave potential cycling diagram of the corresponding blue electrochromic device at its characteristic wavelength.

[0072] Table 1 Comparison of the product performance of each electrochromic device made of the counter electrode obtained in Example 1 and the electrochromic device products made of counter electrodes of other materials

[0073]

[0074] The embodiments of the present invention have been described above. The above description is exemplary and not exhaustive, and is also not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.

Claims

1. An oil-dispersible MHCF nanoparticle, characterized in that: Its molecular formula is KM[Fe(CN)6], wherein M is one or more of nickel, vanadium, chromium, molybdenum, tungsten, manganese, iron, ruthenium, cobalt, platinum and copper metal elements. Oil dispersibility means that in the absence of any other additives, the MHCF nanoparticles are dispersed in an organic solvent to obtain a clear, transparent solution without precipitation; the average particle size of the MHCF nanoparticles is less than 50 nm.

2. The method for preparing oil-dispersible MHCF nanoparticles according to claim 1, characterized in that: The following steps are involved: (a) mixing an aqueous solution of an anionic metal cyano complex containing Fe as the central metal with an aqueous solution of a metal cation compound containing a metal atom M, and performing a coprecipitation reaction at room temperature to generate MHCF nanoparticles; (b) mixing a solution of ligand L dissolved in a solvent with the MHCF nanoparticle suspension obtained in step (a) to perform surface modification, thereby obtaining oil-dispersible MHCF nanoparticles dispersed in the mixed solution; (c) post-treating the solution obtained in step (b) to obtain the oil-dispersible MHCF nanoparticles.

3. The method for preparing oil-dispersible MHCF nanoparticles according to claim 2, characterized in that: In the step (a): The anionic metal cyano complex with Fe as the central metal is Na3Fe(CN)6 or K3Fe(CN)6; The anion of the metal cation compound containing the metal atom M is SO4 2- 、NO 3- , Cl - One of the following, wherein M is one or more of nickel, vanadium, chromium, molybdenum, tungsten, manganese, iron, ruthenium, cobalt, platinum and copper; The molar ratio of the anionic metal cyano complex with Fe as the central metal to the metal cationic compound containing the metal atom M is 1 to 1.5:

1.

4. The method for preparing oil-dispersible MHCF nanoparticles according to claim 2, characterized in that: The temperature of the coprecipitation reaction in step (a) is 25° C., and the reaction time is 3 to 5 hours.

5. The method for preparing oil-dispersible MHCF nanoparticles according to claim 2, characterized in that: In the step (b): The ligand L is oleylamine or stearylamine; The solvent for dissolving the ligand L is one of toluene, dichloromethane, chloroform, hexane and ether.

6. The method for preparing oil-dispersible MHCF nanoparticles according to claim 2, characterized in that: In the step (b): The amount of the ligand L added is relative to the total amount of the metal atom Fe and the metal atom M in the MHCF nanoparticles obtained in step (a), and the molar ratio (Fe+M): L is 1:0.2 to 1:2; The amount of solvent used when dissolving the ligand L is calculated as a mass ratio of ligand L:solvent of 1:5 to 1:50; The MHCF nanoparticle suspension is obtained by dispersing the MHCF nanoparticles obtained in step (a) with water. The amount of water added is calculated according to the volume ratio of the solvent of the ligand L, and the solvent: water is 3:1 to 5:

1.

7. The method for preparing oil-dispersible MHCF nanoparticles according to claim 2, characterized in that: In the step (b), the surface modification treatment temperature is 25° C. and the reaction time is 1 to 3 hours.

8. The method for preparing oil-dispersible MHCF nanoparticles according to claim 2, characterized in that: The method of step (c) is: extracting the mixture obtained in step (b) with a solvent of ligand L, filtering the extracted solution with diatomaceous earth, and then removing the remaining solvent by rotary evaporation to obtain oil-dispersible MHCF nanoparticles.

9. A MHCF film, characterized in that: The oil-dispersible MHCF nanoparticles according to claim 1 are dissolved in a solvent and then sprayed, and then washed with acetone and dried, and the film thickness is 400 to 900 nm.

10. A MHCF counter electrode film, characterized in that: The oil-dispersible MHCF nanoparticles according to claim 1 are dissolved in a solvent and then sprayed on a transparent conductive substrate, and then washed with acetone and dried to form a film with a thickness of 400 to 900 nm. The MHCF counter electrode film has a transmittance of 50% to 99% in the visible light band of 500 nm to 800 nm; and exhibits electrochromic characteristics of anodic coloring during the electrochemical oxidation-reduction process.

11. A polymer electrochromic device, characterized in that: The invention comprises a transparent conductive electrode layer, an electrochromic polymer layer, an electrolyte layer and a counter electrode layer which are sequentially stacked, wherein the counter electrode layer is formed by the oil-dispersible MHCF nanoparticles according to claim 1 on a transparent conductive substrate.